2019
DOI: 10.2478/ama-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Stabilization Controls of a Forklift Vehicle

Abstract: This paper presents the control designs for an autonomous forklift vehicle that drive the vehicle from an initial configuration to a final one. Three stabilization controls, which are chained-form time-varying control, sigma-transformed discontinuous control, and navigation-variables-based discontinuous control, for a forklift vehicle are compared by simulations. The sigma-transformed and navigation-variables-based discontinuous controls provide fast convergence motions from an initial to a final configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The interplay between the physical space and its digital counterpart in the digital twin model is illustrated in Figure 3 1) is a nonhlonomic system, which according to Brockett's theorem (Brockett, 1983), cannot be stabilized by any continuous feedback control algorithm, but may be stabilized by a discontinuous or time-varying one. A comparative study of discontinuous and timevarying controls for an autonomous vehicle was reported in Widyotriatmo (2019) and it was found that the discontinuous controls resulted in faster and more natural motion in pointstabilization control. To introduce the necessary discontinuity, a state variables transformation is performed.…”
Section: Digital Twinmentioning
confidence: 99%
“…The interplay between the physical space and its digital counterpart in the digital twin model is illustrated in Figure 3 1) is a nonhlonomic system, which according to Brockett's theorem (Brockett, 1983), cannot be stabilized by any continuous feedback control algorithm, but may be stabilized by a discontinuous or time-varying one. A comparative study of discontinuous and timevarying controls for an autonomous vehicle was reported in Widyotriatmo (2019) and it was found that the discontinuous controls resulted in faster and more natural motion in pointstabilization control. To introduce the necessary discontinuity, a state variables transformation is performed.…”
Section: Digital Twinmentioning
confidence: 99%